Taxation, Transfer Income and Stock Market Participation - Fischer, Marcel; Jensen, Bjarne Astrup (My University, 2015)
This article studies the impact of a redistributive tax system on consumption, portfolio decisions, and asset prices in a dynamic general equilibrium model. Poorer agents, which receive more in transfers than they pay in taxes, optimally reduce their exposure to equity, because the transfer income the receive is subject to stock market risk. This article thus provides a novel explanation for the low stock market participation rtes of poorer investors.
Keywords: 330; G11; E21; H24